1990
DOI: 10.1128/jb.172.2.525-530.1990
|View full text |Cite
|
Sign up to set email alerts
|

The VirA protein of Agrobacterium tumefaciens is autophosphorylated and is essential for vir gene regulation

Abstract: The virA and virG gene products are required for the regulation of the vir regulon on the tumor-inducing (Ti) plasmid of Agrobacterium tumefaciens. VirA is a membrane-associated protein which is homologous to the sensor molecules of other two-component regulatory systems. We overproduced truncated VirA proteins in Escherichia coli by deleting different lengths of the 5'-coding region of the virA gene and placing these genes under lacZ control. These proteins were purified from polyacrylamide gels and renatured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
114
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 40 publications
(39 reference statements)
3
114
0
1
Order By: Relevance
“…Protein-histidine kinases VirA, ArcB, and EnvZ autophosphorylate in vitro when truncated by removal of transmembrane regions but not when intact (54,55,58). Similarly, we observed phosphorylation in vitro by truncated but not by intact H 6 HepK (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Protein-histidine kinases VirA, ArcB, and EnvZ autophosphorylate in vitro when truncated by removal of transmembrane regions but not when intact (54,55,58). Similarly, we observed phosphorylation in vitro by truncated but not by intact H 6 HepK (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The high proportion of environmental signal transducers and transcriptional regulators could be indicative of the need to respond to changes in the host environment (e.g., osmotic; see above), to control the complex steps of colonization or biofilm formation and to mediate the interactions with other community members. For example, there are many homologs of COG0642 (histidine kinase), members of which are known to be involved in osmoregulation (49), multidrug export (50), sporulation (51), nitrate reduction (52), cell differentiation (53), and plant virulence (54). Also overrepresented is COG0583 (transcriptional regulator), which contains proteins that regulate transcription in response to plant exudates (55), virulence, motility, and quorum sensing (56).…”
Section: Resultsmentioning
confidence: 99%
“…However, Melchers et al have shown that the periplasmic portion is not required for acetosyringonemediated vir gene induction; rather, the two transmembrane sequences may be important (19). The C-terminal half of the VirA protein was shown to possess an autophosphorylating activity in vitro (11,14), and this autophosphorylation is required for its biological activity (14). The phosphorylation site on the VirA protein was identified as a specific histidine residue (14).…”
mentioning
confidence: 99%
“…The C-terminal half of the VirA protein was shown to possess an autophosphorylating activity in vitro (11,14), and this autophosphorylation is required for its biological activity (14). The phosphorylation site on the VirA protein was identified as a specific histidine residue (14). The phosphohistidine is a high-energy phosphate bond and usually exists as a transient state (23).…”
mentioning
confidence: 99%